Development of T-cell engagers selective for cells co-expressing two antigens. Issue 1 (31st December 2022) - Dicara, Danielle M.; Bhakta, Sunil; Go, Mary Ann; Ziai, James; Firestein, Ron; Forrest, Bill; Gu, Chen; Leong, Steven R.; Lee, Genee; Yu, Shang-Fan; Polson, Andrew G.; Agard, Nicholas J.
ABSTRACT: T cell-engaging bispecific antibodies (TCEs) are clinically effective treatments for hematological cancers. While the utility of TCEs in solid malignancies is being explored, toxicities arising from antigen expression on normal tissues have slowed or halted several clinical trials. Here, we describe the development of TCEs that preferentially drive T cell-mediated death against target cells co-expressing two tumor-associated antigens. We show that Ly6E and B7-H4 are simultaneously expressed on approximately 50% of breast cancers, whereas normal tissue expression is limited and mostly orthogonal. Traditional bispecific TCEs targeting a singular antigen, either Ly6E or B7-H4, are active when paired with high-affinity CD3-engagers, but normal tissue expression presents a toxicity risk. Treatment with a murine cross-reactive B7-H4-TCE results in rapid and severe weight loss in mice along with damage to B7-H4-expressing tissues. To overcome on-target toxicity, we designed trispecific antibodies co-targeting Ly6E, B7-H4, and CD3 and characterized the impact of dual-antigen binding and the relative placement of each binding domain on tumor killing in vitro and in vivo. In vitro killing of tumor cells co-expressing both antigens correlates to the placement of the higher affinity B7-H4 binding domain, with only modest enhancements seen upon addition of Ly6E binding. In xenograft models, avid binding of appropriately designed trispecific TCEs enables tumor growth inhibition while evading the poor tolerability seen with active bispecific TCEs. Collectively these data highlight the potential for dual-antigen targeting to improve safety and efficacy, and expand the scope of tumors that may effectively be treated by TCEs. Abbreviations: Chimeric antigen receptor T cells (CAR-Ts), dual-antigen targeted T cell engagers (DAT-TCE), Fragment antigen-binding (Fab), Hematoxylin and eosin (H&E), Institutional Animal Care and Use Committee (IACUC), Immunoglobulin G (IgG), immunohistochemistry (IHC), NOD SCID gamma (NSG), peripheral blood mononuclear cells (PBMCs), surface plasmon resonance (SPR), T cell-engagers (TCEs)